Analysis of Financial Reports In An Effort To Assess The Feasibility of Financial Performance At PT. Ruvi Rizqy Berkah - Runiar Satriya; Dwi Widi Hariyanto (Faculty of Economics Merdeka University Surabaya Jl. Ketintang Madya VII/2 Karah, Kec. Jambangan, Kota SBY, Jawa Timur 60232, 2023)
The development of an increasingly competitive business world requires every company to can process the company's resources to be more professional. The purpose of this study, among others, to determine the existence of PT. Ruvi Rizqy Berkah with its financial performance fulfills business feasibility during the current period. To find out the development of PT. Ruvi Rizqy Berkah with his financial performance in the coming period. To find out the whereabouts of PT. Ruvi Rizqy Berkah to his ability to independently expand or use foreign capital. The type of research used is descriptive qualitative. The population in this study are all financial statements of PT. Ruvi Rizqy Berkah. The sample of this research is the financial statements of PT. Ruvi Rizqy Berkah for the 2017-2019 book closing period. The data analysis step is to measure the data and evaluate how the company's financial performance is using the Liquidity Ratio, Solvency Ratio, Activity Ratio and Profitability Ratio. Based on the results of the analysis that has been done, it can be concluded as follows PT. Ruvi Rizqy Berkah has good financial performance and fulfills business feasibility during the current period, the development of PT. Ruvi Rizqy Berkah with its financial performance in the coming period is still fluctuating, this is shown by the value of financial ratios which include solvency, profitability and activity which have decreased and increased, while the liquidity ratio shows the direction of decline and PT. Ruvi Rizqy Berkah has the potential to have the ability to independently expand or use foreign capital as evidenced by the fact that there are quite a lot of outlets or branches that require investors to develop their business, this can be seen in the high asset turnover, namely the value of the company's activity ratio